2000
DOI: 10.1097/00008571-200008000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the bilirubin uridine-diphosphoglucuronosyl transferase 1A1 gene in healthy Taiwanese

Abstract: The activity of uridine-diphosphoglucuronosyl transferase 1 (UGT1) may influence the concentration of serum bilirubin. Because UGT1 is too labile to be measured with classical biochemical methods, we analysed the whole UGT1A1 gene in 290 healthy Taiwanese adults by using the polymerase chain reaction method, and investigated the relationship between UGT1A1 genotypes and serum bilirubin levels. The results showed that slightly more than 50% of the subjects had one or more variant sites in UGT1A1 gene. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
87
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 17 publications
17
87
3
Order By: Relevance
“…[16][17][18] In the present study, the (TA)7 allele was significantly associated with higher T-Bil concentrations, in line with previous reports. 15,19 However, different to Koreans, no association between 211A allele and bilirubin level was found. Carriers of the haplotypes 4 (À3279G; À3156A; (TA)7; 211G; 686C) had increased serum T-Bil concentrations compared with the other groups.…”
Section: Intra-ethnic Differences In Genetic Variantsmentioning
confidence: 71%
See 1 more Smart Citation
“…[16][17][18] In the present study, the (TA)7 allele was significantly associated with higher T-Bil concentrations, in line with previous reports. 15,19 However, different to Koreans, no association between 211A allele and bilirubin level was found. Carriers of the haplotypes 4 (À3279G; À3156A; (TA)7; 211G; 686C) had increased serum T-Bil concentrations compared with the other groups.…”
Section: Intra-ethnic Differences In Genetic Variantsmentioning
confidence: 71%
“…10 Association between increased serum T-Bil levels and genetic variants of UGT1A1 was reported in healthy Koreans and Taiwanese. 14,15 A significant correlation between SN-38 and bilirubin glucuronidation has been found, high serum T-Bil concentration seemed to be a reasonably good predictor of lower irinotecan clean rate. [16][17][18] In the present study, the (TA)7 allele was significantly associated with higher T-Bil concentrations, in line with previous reports.…”
Section: Intra-ethnic Differences In Genetic Variantsmentioning
confidence: 95%
“…The most common nonsynonymous single-nucleotide polymorphism (SNP) (211GϾA) that causes an amino acid alteration (glycine to arginine at codon 71) is found in Asian populations at frequencies of 13-23% (7,8 ). The 686CϾA (P229Q) variation in the Taiwanese has a frequency of 2.8% (8 ).…”
mentioning
confidence: 99%
“…The UGT1A1*6 polymorphism, causing a G→A substitution in the first exon, is a common SNP in the Asian population, but is rare in the Caucasian and African populations (Huang et al, 2000). Our study demonstrated the potential association of the UGT1A1*6 SNP with the development of breast cancer in a Chinese population for the first time.…”
Section: Discussionmentioning
confidence: 53%